Tenosynovial Giant Cell Tumor, Localized Type With Extensive Chondroid Metaplasia: A Case Report With Immunohistochemical and Molecular Genetic Analysis. (June 2020) - Nagase, Mamiko; Araki, Asuka; Ishikawa, Noriyoshi; Nagano, Nahoko; Fujimoto, Makiko; Biyajima, Kyoko; Yamagami, Nobuo; Yamamoto, Soichiro; Maruyama, Riruke
Tenosynovial giant cell tumor (TSGCT) of localized type is a common disease occurring mostly in the hands. Diagnosis of this tumor is relatively easy to render with hematoxylin-eosin–stained sections as compared with that of TSGCT of diffuse type. However, very rare cases with chondroid metaplasia that have recently been reported mainly in diffuse type can make pathological differentiation from soft tissue cartilaginous tumors extremely difficult. In this article, the authors present the second reported case of TSGCT of localized type showing extensive chondroid metaplasia. Pathological interpretation was difficult without utilizing immunohistochemistry and fluorescence in situ hybridization. One must be careful not to misdiagnose this lesion as cartilaginous tumors of soft tissue, and we suspect at least some chondroblastoma-like chondroma could be reclassified as TSGCT of localized type with extensive chondroid metaplasia. Morphological, immunohistochemical, and molecular genetic characteristics are presented and discussed.